PERLINDUNGAN HUKUM BAGI INVESTOR DALAM MEMANFAATKAN TANAH ULAYAT DI PAPUA - Kaidati, Vherza Istiqomah; I Dewa Ayu Widyani; Thomas Abbon (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Papua has great natural resources, making it investors interested in making efforts or investing in Papua. The problem of ulayat land in Papua is very complicated if it is possible that the conflict and claim of the land of the Ulayat land. The demands of indigenous pigs trigger the occurrence of conflict, so that will eventually win one of the tribes from the customary law community. This will make other customary laws to want the same compensation and make the tribe that will make a claim. The customary law community argues that with the admissions of existence of customary land, then other parties such as investors can get the right to the right of the customary land, when it has been made by the customary. In relation to that the need for legal protection against investors in obtaining rights of land in Papua, especially the ulayat land. The method of research that the author applied in the pharmacity of this study is the normative juridis, namely legal research that prioritizes secondary data, namely data obtained from library materials related to the topic studied in the form of books and Law Number 5 of 1960 on the basic regulations of the agricultural points. As well as this research is done by applying legislation, sociological approach, concept approach. The results of this research the show is that the agrarian principal law has been enacted in Papua, but the transition of land is more accommodated through customary transition. The customary land transition can be given the ease of ensuring legal protection for investors when it is done in accordance with the tradition of Papuan law, as the majority of Papuan land of people still holds the principle that customary law is applicable in Papua. Indulge of Induasi namely Pindasus Number 23 of 2008 concerning the right to UKPAIN customary law and individual rights of citizens of customary laws on the land. The recognition of the ultimate rights in this peripulate uses the national legal logic that is sourced from the government based on determination.